KORELASI ANTARA BOBOT BADAN DAN DIMENSI TUBUH PADA SAPI PERANAKAN ONGOLE JANTAN PADA UMUR 7—12 BULAN DI DESA WAWASAN KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Ersi, Fauzan; Hamdani, M. Dima Iqbal; Sulastri, Sulastri; Adhianto, Kusuma (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
The aim of the research to know correlation size between body weight and body dimensions in male Ongole Crossbreed cattle of age 7—12 months. This research was held in July—August 2018 on Ongole Breeding Centre at Wawasan Village, Tanjungsari District, South Lampung Regency The research used survey method. Data collection was done by taking measurement body weight and body dimension on male Ongole Crossbreed Cattle of age 7—12 month from 30 head Ongole Crossbreed cattle at 4 farmer groups in Wawasan Village. Data were doing based on groups analyzed using correlation analysis. The highest value of quantitative perfomance is Marga Jaya IV livestock groups (body weight 110.5±17.62 kg, body length 95.66±10.69 cm, chest size 124.5±9.35 cm, back height 113.16±8.81 cm, head width 18.33±1.03 cm, head length 42.16±2.31 cm), while the lowest value of quantitative perfomance in Bumi Asih Sejahtera livestock groups (body weight 93.75±19.86 kg, body length 90.37±14.33 cm, chest size 114.87±11.26 cm, back height 107.5±11.80 cm, head width 16.87±2.58 cm, head length 38.87±6.03 cm). The result showed the correlation in Wawasan Village, Tanjungsari District, South Lampung Regency it was 0,72. In conclusion of the research results between body weight and body dimensions has a high correlation. Keywords: Correlation, Body weight, Body dimensions, Ongole Crossbreed Cattle